2016
DOI: 10.18632/oncotarget.6886
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 regulates melanoma invasion and metastasis through ubiquitination of Basigin

Abstract: TRAF6 plays a crucial role in the regulation of the innate and adaptive immune responses. Although studies have shown that TRAF6 has oncogenic activity, the role of TRAF6 in melanoma is unclear. Here, we report that TRAF6 is overexpressed in primary as well as metastatic melanoma tumors and melanoma cell lines. Knockdown of TRAF6 with shRNA significantly suppressed malignant phenotypes including cell proliferation, anchorage-independent cell growth and metastasis in vitro and in vivo. Notably, we demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 40 publications
(42 reference statements)
6
68
0
Order By: Relevance
“…In this study, we found that EGCG significantly attenuated the proliferation and metastasis of melanoma (Figure 5), a finding that is consistent with the results of our previous study concerning the effects of TRAF6 in melanoma [23]. NF-κB is member of a family of proteins including RelA (p65), RelB and c-Rel [61] that form homo- or heterodimers and bind to specific sequences in promoter regions in response to extracellular stimuli, such as inflammation, cytokines, and tumor promoters.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that EGCG significantly attenuated the proliferation and metastasis of melanoma (Figure 5), a finding that is consistent with the results of our previous study concerning the effects of TRAF6 in melanoma [23]. NF-κB is member of a family of proteins including RelA (p65), RelB and c-Rel [61] that form homo- or heterodimers and bind to specific sequences in promoter regions in response to extracellular stimuli, such as inflammation, cytokines, and tumor promoters.…”
Section: Discussionsupporting
confidence: 92%
“…Al‐Azayzih observed that stimulation with TGFβ1 induced prostate tumour cell scattering and increased expression of Snail and N‐cadherin through TRAF6‐mediated activation of Rac1/Pak1 pathway . TRAF6 knockdown can significantly decrease invasion and metastasis abilities in melanomas and lung cancer . In the present study, we found that TRAF6 was highly expressed in SCCHN cell lines.…”
Section: Discussionsupporting
confidence: 62%
“…The TM domain of Basigin consists of a stretch of ≈23 highly hydrophobic residues, which are found to be highly conserved among species . Basigin is a TM protein, but it is also known to be localized in the cytoplasm and mitochondria . Basigin encourages MMP over‐expression in tumor cells by stimulating adjacent fibroblasts and regulates cancer progression .…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin is transferred from E2 to the substrate, and the substrate is either marked for degradation or localization. It mediates K‐63 linked ubiquitin tagging of substrates . It is known to be involved in many cellular pathways by interacting with the intercellular domains of many receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation